Foreigner and foreign in English-language newspapers in Malaysia: A framesemantic approach - Toshiko Yamaguchi; Huixin Yeo (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2015)
This paper explores the usage of two morphologically related words, foreign and foreigner, in two major daily English-language newspapers circulated widely in Malaysia. On the basis of 285 tokens, the study shows a striking tendency indicating that they do not share exactly the same semantic content. While foreign is used neutrally to modify things or people from a country other than Malaysia, foreigner is found frequently in four negative contexts (running illegal businesses, entering Malaysia illegally, bringing diseases to Malaysia, and misusing marriage in Malaysia). Using Fillmore’s frame as a theoretical construct, the study seeks to explain why foreigner tends to correlate with negative connotations, while foreign does not. The central idea is that the PERSON attribute attached to foreigner invokes positive/neutral and negative values, and that the semantics of foreigner and foreign incorporates our schematic knowledge about everyday life. In conclusion, these results are stated to shed light on ‘the changing tenor of English’ in Malaysia.